2021
DOI: 10.1021/acsanm.1c02845
|View full text |Cite
|
Sign up to set email alerts
|

Guanidinium-Based Ionic Covalent-Organic Nanosheets for Sequestration of Cr(VI) and As(V) Oxoanions in Water

Abstract: Chromium- and arsenic-based oxoanions are among the major highly toxic and carcinogenic inorganic pollutants present in groundwater, demanding fast and selective sequestration. Efficient capturing and removal of these highly mobile oxometallates at neutral pH presents a great challenge in groundwater cleanup. Herein, a series of guanidinium-based ionic organic covalent nanosheets (iCONs) with varying hydrogen bonding, steric, and electronic properties was studied to examine the structure–activity relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…XPS was used to monitor the protonation and deprotonation processes (Figures and S9). It has been reported that condensation between TG Cl and di- or tricarboxaldehyde led to ionic COFs with protonated guanidinium units and chloride counteranions. The photoelectron signal of Cl – was not observed for the as-synthesized TG-DMPZ but appeared in the spectrum of the HCl-acidified sample. The results suggest that TG-DMPZ was synthesized as a neutral COF and that acidification led to an ionic one with guanidinium groups.…”
Section: Resultsmentioning
confidence: 98%
“…XPS was used to monitor the protonation and deprotonation processes (Figures and S9). It has been reported that condensation between TG Cl and di- or tricarboxaldehyde led to ionic COFs with protonated guanidinium units and chloride counteranions. The photoelectron signal of Cl – was not observed for the as-synthesized TG-DMPZ but appeared in the spectrum of the HCl-acidified sample. The results suggest that TG-DMPZ was synthesized as a neutral COF and that acidification led to an ionic one with guanidinium groups.…”
Section: Resultsmentioning
confidence: 98%
“…Further, it was observed that the adsorption capacity of iCON-5 diminished to the greatest extent upon exposing it to an aqueous environment with pH 10 or more. This could be attributed to the partial loss/neutralization of the positive charge on the surface of iCON-5 in the presence of a high concentration of hydroxide ions at pH greater than 10. , The enthalpy of adsorption is an important parameter to evaluate the adsorption property relationship. In this regard, we performed kinetic experiments of MnO 4 – adsorption on iCON-5, and the enthalpy of hydration was estimated using the formulas mentioned in the Experimental Section.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, ionic covalent organic networks are an emerging class of functional materials that are deliberately incorporated with ionic interfaces for inducing strong and attractive interactions with oppositely charged species. [54][55][56][57][58][59][60] Herein, we report the design and synthesis of an ionic covalent organic network (iCON-4) decorated with ionic functionalities and imine linkages for superior interaction with iodine. A Schiff-base polycondensation reaction was applied to obtain iCON-4 without using any acid or metal catalyst.…”
Section: Introductionmentioning
confidence: 99%